Dukungan Institusi Pendidikan Kesehatan dalam Rangka Akselerasi Bulan Imunisasi Nasional di Kecamatan Johar Baru - Indriati Kusumaningsih; Dewi Novitasari Suhaid; Marta Cici Haryati (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Abstrak – Immunization in toddlers is an effort to provide active immunity to prevent transmission of diseases that can be prevented by vaccination. Complete basic immunization coverage has decreased significantly since the start of the COVID-19 pandemic. This resulted in the discovery of several extraordinary cases of Measles and Rubella. The Indonesian government launched a strategy to accelerate coverage by holding the National Immunization Month (BIAN). This activity is oriented towards providing additional immunizations and complementing the immunization status of children who are left behind. During this acceleration, the Johar Baru District Health Center invited Sint Carolus School of Health Sciences to provide services aimed at improving the health status of the community in their working area. The activity was caried out on August 2-26th 2022 at 14 Posyandu involving lectures, students, health workers, and the health cadres. Posyandu implementation focuses on immunization activities. Adjusted immunization results based on targets in an average area of 53%. Integrated collaborative activities that involve stakeholders by health facilities are one of the efforts in equal distribution of basic health services covering certain areas. Apart from being one of the Three Dharma of Higher Education, this activity also contributes to improving public health status.